IMPROVING SPEAKING ABILITY OF THE ELEVENTH YEAR STUDENTS OFSMA LABORATORIUM UNSYIAH BANDA ACEH BY USING TIMETOKEN ARENDS TECHNIQUE - Sukmayati (Getsempena English Education Journal, 2014)
This research is intended to investigate the effect of Time Token Arends Technique application in teaching speaking to the eleventh grade students of Senior High School (SMA) LaboratoriumUnsyiah Banda Aceh. The main purpose was to know whether the students who were taught by using Time Token Arends Technique would get a better performance in their speaking compared to those who were not. The topic given to the students was the expression of asking and giving opinion and suggestion. The population and sample of the study was the eleventh year students of SMA LaboratoriumUnsyiah Banda Aceh which consists of 58 students; 29 in each class. The data of this research was collected by giving the pre-test and post-test. The data was analyzed using statistical formula including mean, standard deviation, and t-test. The result of the data analysis can be seen from the result of the post-test of the experimental and the control group. The mean of the post-test of the experimental group was 48,97 while the mean of the control group was 38,10. The mean score of the pre-test of the experimental group was 35,52 and the mean score of the experimental group was 48,97. In order to prove the hypothesis, the t-test score of the experimental group was compared with t-table score, it shows that the result of t-test of the post-test of experimental group was 2,279 while the result of t-table at a level of significance with a = 0,05 is 2,048. It indicates that the t-test score is higher than the t-table 2,048. It means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So, it can be concluded that the students who were taught by using Time Token Arends Technique have a better performance than those who were not. As the follow up for this research, it is suggested that English teachers should use various technique in teaching. In teaching speaking, Time Token Arends Technique can be an alternative technique to be applied.